RARE-56. PERITONEAL SEEDING OF A DIFFUSE LEPTOMENINGEAL GLIONEURONAL TUMOR IN A CHILD. (4th December 2020) - Messiaen, Julie; Uyttebroeck, Anne; Depreitere, Bart; Bempt, Isabelle Vanden; Sciot, Raf; Jacobs, Sandra A
Abstract: Diffuse leptomeningeal glioneuronal tumors (DLGNT) are rare neoplasms of the central nervous system and have been included in the 2016 update of the WHO classification. This is the first description of a DLGNT disseminating to the peritoneal cavity via a ventriculoperitoneal shunt (VPS) in a child. We describe an 11-year old girl who received a VPS for a Dandy-Walker malformation at the age of seven, and was diagnosed with a spinal pilocytic astrocytoma with leptomeningeal metastases six months later. She received chemotherapy (SIOP-LGG protocol) with partial response, and had progressive disease eight months after therapy cessation. Following a novel biopsy, the diagnosis was revised to a DLGNT, with a KIAA1549-BRAF fusion and loss of 1p. She received vinblastine, but was clinically progressive and craniospinal radiotherapy was initiated. 13 months later, she suddenly presented with ascites. The inferior vena cava was compressed due to the ascites, and an abdominal drain was placed, with massive fluid release. Abdominal MRI indicated an omental cake and peritoneal contrast enhancement. Bone metastases were suspected in the iliac and femoral bones. Anatomopathological examination of the ascites showed an atypical cell population, with irregular, hyperchromatic and enlarged nuclei resembling the primary tumor. The cells were positive for synaptophysin, MAP2 and weakly positive for S100. Pan-NTRK staining was negative. The diagnosis of a metastatic localization of the DLGNT was made, due to seeding of tumoral cells via the VPS. Treatment with a MEK-inhibitor was initiated, but was stopped due to progressive disease and she died 3 weeks later.